Conformity of the Employment Agreement With the Implementation Related to the Pension Fund in Pensioners - Miryam Cahya Pramesti; Johnson Dongoran (Quantitative Economics and Management Studies, 2023)
Wages in old age are very important because life in the old age must have welfare, especially when health is no longer able to support to work properly. Pension funds are something that is highly expected by retirees because work productivity has decreased. Welfare obtained from pension funds is a form of agreement at the outset that must be in accordance with the rights and obligations of workers. From various previous studies, it was found that there is a discrepancy in the practice of pension fund agreements that workers should receive. This study aims to find out and help retirees to convey if there is a discrepancy with the rights they should get from DAPENMA, and help retiree participants to simplify problems regarding updating data that experience several obstacles. This study used a qualitative method by collecting primary data obtained by interviews and questionnaires to DAPENMA PAMSI pension participants. The sample obtained in this study was 31 data on retired participants. The implementation of the pension funds received by participants is in accordance with what was promised by the DAPENMA PAMSI Institution and is in accordance with the government regulation of the Republic of Indonesia no. 76 of 1992 concerning the Employer Pension Fund CHAPTER IV concerning the Rights of participants. And updating data that is felt to have problems by participants is also caused by both parties